2006
DOI: 10.1017/s0950268806007266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV infection among young adult injecting and non-injecting heroin users in Spain in the era of harm reduction programmes: gender differences and other related factors

Abstract: The aims were to assess the prevalence of HIV infection among young adult heroin users, including injecting heroin users (IHUs) and non-injecting heroin users (NIHUs), and to explore the differences by gender and other factors. The design was a cross-sectional cohort study between April 2001 and December 2003, which included 961 current heroin users (HU), aged 18-30 years: 422 in Madrid, 351 in Barcelona and 188 in Seville; 621 were IHUs and 340 were NIHUs. All were street-recruited by chain referral methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
2
11
2
1
Order By: Relevance
“…Several studies have shown that crack cocaine users engage in more unprotected sexual acts, trade sex for money or drugs and have more sexually transmitted diseases, all factors contributing to greater risk for HIV infection [17,21,[23][24][25][26]. One third of the study participants had a history of injection drug use, but no associations were identified between IDU and HIV infection in males or females in this study, a conflicting finding from other studies [27][28][29][30][31]. Therefore, crack cocaine use and resulting sexual behaviors from its use infer the most likely way HIV is transmitted amongst drug users in this population.…”
Section: Discussioncontrasting
confidence: 79%
“…Several studies have shown that crack cocaine users engage in more unprotected sexual acts, trade sex for money or drugs and have more sexually transmitted diseases, all factors contributing to greater risk for HIV infection [17,21,[23][24][25][26]. One third of the study participants had a history of injection drug use, but no associations were identified between IDU and HIV infection in males or females in this study, a conflicting finding from other studies [27][28][29][30][31]. Therefore, crack cocaine use and resulting sexual behaviors from its use infer the most likely way HIV is transmitted amongst drug users in this population.…”
Section: Discussioncontrasting
confidence: 79%
“…Furthermore, 46.8% of the individuals reported performing the test in the private healthcare network, which highlights the need to widen free access to the test. Finally, the prevalence of self-reported HIV infection was 3.2% (95% CI: 1.4-7.2%), similar to that estimated for NIDU in Argentina (14), Luxembourg (13), Spain (12), and Mexico (11). However, it was lower than that found in the USA (15).…”
Section: Discussionsupporting
confidence: 74%
“…Studies have shown elevated prevalence of HIV infection among NIDU worldwide, ranging from 3.7% in México to 16.0% in the United States of America (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The closer the proximity of injecting partners/peers, the less perceived risk with sharing injecting equipment (MacRae & Aalto, 2000;Smyth & Roche, 2007). Women who inject drugs are often marginalised and socially isolated, and as a result often engage in smaller social networks increasing the likelihood of sharing injecting equipment (De et al, 2007). A high proportion of female drug users meet criteria for a depressive disorder (Torrens et al, 2011).…”
Section: Increased Risk Of Hcv Among Females Who Inject Drugsmentioning
confidence: 99%
“…The risk of sexual acquisition of HCV for HIV negative women is extremely low. HCV prevention interventions for people who inject drugs may result in their rationalising sharing injecting equipment with a sexual partner they are having unprotected sex with, if they perceive an equivalent risk of HCV from both behaviours (Harris & Rhodes, 2013 (Barrio et al, 2007). Moreover, in countries such as Poland, with elevated HIV prevalence among people who inject drugs (18%), co-infection with HCV is reported to be 17% (Rosinska et al, 2015).…”
Section: The Need For Gender Sensitive Interventionsmentioning
confidence: 99%